DISIPLIN PEGAWAI NEGERI SIPIL DALAM MELAYANI PEMBUATAN SURAT KETERANGAN GANTI RUGI PADA KANTOR CAMAT TAMPAN KOTA PEKANBARU - Yuda, M. Fadli; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research based on of a problem from a phenomenon that happened at TampanDistrict Office, Pekanbaru. The phenomenon that happened there is employees, who lessdiscipline. This case is seen from some employees who do service in making indemnity letterat Tampan District.The purpose of this research is to find out how discipline the employee of civil servantemployees in making service of indemnity letter and what factors that affect the civil servantemployees at Tampan District Office, Pekanbaru. This research used discipline theory fromMalayu S.P Hasibuan and to find out the factors that affect the of employee’s discipline.The result of this research showed that, the discipline of civil servant in makingservice of indemnity letter at Tampan District Office Pekanbaru, have done, but there aresome aspect that is not as appropriate as wishing. The deviation of employees in service isthe priority attention, and the influencing factors like the lack of observation by the leader,uneffective attendance list and the influencing factors like the lack of applying disciplinepenalization for the employees of Tampan District Office, Pekanbaru.Keywords: Discipline, Employee Discipline and Service